Le mobile professionnel : un outil de conciliation ou de confinement dans la charge du care pour les femmes cadres ? - Catherine Lejealle (Temporalités)
In all social classes, women are more responsible for family care than men. Professional mobile telephones are compulsory for executives but represent a threat for female executives, as they can serve to increase the gender gap and impede careers. Women can be reached anywhere anytime on their company-paid mobile by children, spouses or other relatives seeking their help or support. Thus, female executives are compelled to invent solutions, such as personalized ring tones to avoid private incoming calls while looking to minimize the number and duration of private outgoing calls. Their unpredictable timetables make it all the harder to organize the household out of the ear-shot of colleagues.